2012
DOI: 10.1074/jbc.m112.361824
|View full text |Cite
|
Sign up to set email alerts
|

Histone Monoubiquitylation Position Determines Specificity and Direction of Enzymatic Cross-talk with Histone Methyltransferases Dot1L and PRC2

Abstract: Background: "Designer" nucleosomes are key tools to investigate functions of histone modifications. Results: Histone H2Aub inhibits PRC2 methylation of histone H3 Lys-27 but not Dot1L methylation of H3 Lys-79. Conclusion: The position of nucleosome monoubiquitylation affects the specificity and direction of cross-talk with histone methyltransferases. Significance: Cross-talk between histone modifications and chromatin enzymatic activities may be an important mechanism for generating distinct biological outputs. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…The methylation of H3K79 by DOT1/DOT1L results from transhistone cross-talk that was initially found in combination with mono-ubiquitylation of H2B at K123 and K120 in yeast and mammals, respectively (Briggs et al, 2002;Krogan et al, 2003;Ng et al, 2003b;Ng et al, 2002;Sun and Allis, 2002;Wood et al, 2003). However, recent reports showed that several other types of H2B K ubiquitylation could lead to H3K79 methylation (Chatterjee et al, 2010;Whitcomb et al, 2012;Wu et al, 2011). Therefore, although exclusively catalyzed by DOT1/DOT1L, the methylation of H3K79 is a complex event in which several protein complexes are involved.…”
Section: Discussionmentioning
confidence: 99%
“…The methylation of H3K79 by DOT1/DOT1L results from transhistone cross-talk that was initially found in combination with mono-ubiquitylation of H2B at K123 and K120 in yeast and mammals, respectively (Briggs et al, 2002;Krogan et al, 2003;Ng et al, 2003b;Ng et al, 2002;Sun and Allis, 2002;Wood et al, 2003). However, recent reports showed that several other types of H2B K ubiquitylation could lead to H3K79 methylation (Chatterjee et al, 2010;Whitcomb et al, 2012;Wu et al, 2011). Therefore, although exclusively catalyzed by DOT1/DOT1L, the methylation of H3K79 is a complex event in which several protein complexes are involved.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, this histone nicely illustrates the sophistication of modern EPL strategies. Especially notable is the work of Fierz and colleagues (89, 117) on the preparation of H2A ubiquitylated at Lys-119 (H2AK119Ub). The semisynthesis was designed around three building blocks, two recombinant α-thioesters (produced by thiolysis of intein fusions) and a branched synthetic peptide.…”
Section: Semisynthesis Applied To Histonesmentioning
confidence: 99%
“…Further, this linkage enables the dynamic removal of a protein modification via reduction of the disulfide bond, mimicking the dynamic behavior of protein modifications under controlled conditions. The Muir Laboratory exploited this approach to determine the position-dependent effect of ubiquitin in histones H2A and H2B while demonstrating that H2B ubiquitylation perturbs chromatin compaction[80, 81]. A similar approach was used to prepare histone H4 with sumoylation at H4-K12 in the N-terminal tail, and demonstrated that SUMO-3 inhibits higher order chromatin structure required for chromatin compaction [12].…”
Section: : Chemical Installation Of Ptm Analogs At Single Cysteine Smentioning
confidence: 99%